The Influence of Evangelicalism on Government Funding of Faith-Based Social Service Organizations - Ebaugh, Helen Rose Fuchs (Review of religious research, 2006)
Charitable Choice and President Bush's Faith-Based and Community Initiative assume, among other things, that conservative/evangelical religious bodies do a better job of providing social services than many secular agencies and therefore should be entitled to government funding. The question remains of whether evangelical bodies want government aid and will apply for it. We develop two measures of evangelical influence and three scales of religious policies and practices toward clients, staff, and the wider community, using data from a national sample of 656 faith-based social service coalitions. Evangelical influence measures are positively related to the religiosity scales. All five measures are negatively related to attitudes towards government funding, actively seeking it, and actually obtaining funds. Ironically, more religiously conservative coalitions are significantly less likely to want government funding.